Enlightened leadership behaviors and their role in effective management of organizational crises "An analytical study of the opinions of a sample of employees in the presidency of the University of Sulaymaniyah" - Daroon Faridun Abdullah (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
This research aims to identify the role of enlightened leadership behaviors with its dimensions (pacemake, developer, servant, changer, visionary and communicator) in effective management of the organizational crisis with its stages (early warning, preparedness and prevention, containment the damage and its reduction, restore balance and activity, and strategic learning) in the presidency of Sulaimani University. After reviewing the literature, the conceptual framework, study modes and hypothesis were written based on the enlightened leadership and effecitive management of organizational crisis stages. In order to collect the data, the questionnaire tool were used and distributed randomly to the research sample represented by the staff and employees with (65) person in the presidency of Sulaimani University. The population includes (143) person. A number of tests were carried out before and after the distribution of questionnaire in order to verify their validity, reliability, and to ascertain their validity in measuring the variables of the study such as the the validity, reliability (cronbach’s alpha), as well as apply normal distribution (normality) test to ensure that the data is fit and suitable before analysing by using the SPSS v21 program. In order to measure the strength of the correlation and regression between the study variables, several statistical methods were used including simple correlation analysis and simple linear regression. The results showed that there is a positive relationship and effect between the variables and their dimensuions. Based on the results, a number of recommendations were given regarding the need for administrative leaders in the sulaimani university pesidency to focus on following the behaviors of the enlightened leadership in order to be able to achieve effective management of the organizational crisis.